Heterotrimeric G-Protein γ Subunit CsGG3.2 Positively Regulates the Expression of CBF Genes and Chilling Tolerance in Cucumber - Bai, Longqiang; Liu, Yumei; Mu, Ying; Anwar, Ali; He, Chaoxing; Yan, Yan; Li, Yansu; Yu, Xianchang (Frontiers in Plant Science, 2018)
Heterotrimeric G proteins composed of α, β, and γ subunits are central signal transducers mediating the cellular response to multiple stimuli in eukaryotes. Plant Gγ subunits, divided into A, B, and C three structurally distinct types, provide proper cellular localization and functional specificity to the heterotrimer complex. Here, we demonstrate that a type C Gγ subunit CsGG3.2 is involved in the regulation of the CBF regulon and plant tolerance to cold stresses in cucumber (Cucumis sativus L.). We showed that CsGG3.2 transcript abundance was positively induced by cold treatments. Transgenic cucumber plants (T1) constitutively overexpressing CsGG3.2 exhibits tolerance to chilling conditions and increased expression of CBF genes and their regulon genes. Antioxidative enzymes, i.e., superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and glutathione reductase (GR) activities increased in cold-stressed transgenic plants. The reactive oxygen species (ROS), Oxygen free radical (OFR) and H2O2, production, as well as membrane lipid peroxidation (MDA) production decreased in transgenic plants, suggesting a better antioxidant system to cope the oxidative-damages caused by cold stress. These findings provide evidence for a critical role of CsGG3.2 in regulating of cold signal transduction in plant cells.